The effects of analogy teaching on sport skill acquisition in children - Mohsen AFROUZEH; Ferman KONUKMAN; Rabiu Muazu MUZA; Mohammad Sadeq AFROOZEH4; Ertan TUFEKCIOGLU; Bijen FILIZ (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: Teaching motor skills to novices has been the main task of physical educators, and studies in motor learning have always sought to discover better ways to optimize the skill acquisition process. Movement information is presented transparently through the performer's demonstration, illustration, feedback, and verbal guidance in motor skills instructing. This study seeks to determine the type of learning, i.e., analogy learning or explicit learning, suitable for promoting the children's acquisition of skills that are biomechanically and kinematically different from the same skill learned by explicit instructions, and to determine how the physical form of the skill evolves over practice. Material and Methods: Forty-five right-handed healthy beginner male students (mean age 9.93 ±0.55 years; height 1.39 ±4.16 m; body mass 31.65±3.23 kg; novice in basketball) participated in the study. Subjects were randomly allocated to an explicit learning condition (n = 15), an analogy learning condition (n = 15), or an uninstructed control condition (n = 15). Ten free throws (FT) in the standing position were performed with the right hand by each student using modified equipment i.e., a small ball, customized rim with 45-cm circumference and adapted net height of 2 m. Attempts were recorded from 3 m away in a biomechanical laboratory with two-dimensional (2D) video data collection (i.e., using 240 Hz camera resolution). Results: The independent ANOVA yielded a statistically significant effect across the three groups in post-tests: F (8,16) = 283.233, P = 0.001, η2 = 0.793. A statistically significant difference was observed across the three groups: F (8, 16) = 332.057, P = 0.001, η2 = 0.818. Discussion: The analogy group's performance was significantly better in the skill taught. The explicit learners achieved lower scores compared to the analogy learners. Conclusions: The analogy learning training method is recommended for children aged 10-12 willing to learn FT in basketball. The conclusions may be important for coaches concerning the use of different training methods in skill learning.